The differentiated impacts and constraints of allometry, phylogeny, and environment on the ruminants’ ankle bone - Orgebin Pierre; Ilya Dziomber; Aiglstorfer Manuela; Mennecart Bastien (Communications Biology)
Abstract The astragalus is a hinged bony organ common to many tetrapods. Several factors, including allometry, phylogeny, and environment, constrain its morphology. Due to the underlying risk of these factors being confounding, previous works have frequently highlighted the difficulty in discerning the specific influence of each factor. Here, we conducted allometric and size-adjusted clade and ecomorphological analyses to assess the contribution of each of these three parameters to the morphological variation of the astragalus in ruminant artiodactyls. 3D geometric morphometric analyses confirm the astragalus’ highly integrated structure and multifactorial morphological responses. Sturdier astragali are correlated with heavier bodies. Bovids tend to display larger proximal trochlear ridges, and moschids show a prominent posterior process. The degree of development of areas where joints and ligaments intersect reflects the degree of freedom of the ankle and the locomotion type. This study provides new perspectives on the evolution of ruminants and their interactions with their environment.